2019
DOI: 10.1186/s13019-019-0864-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preoperative risk factors and postoperative indicators for anastomotic leak of minimally invasive McKeown esophagectomy: a single-center retrospective analysis

Abstract: Background Minimally invasive McKeown esophagectomy is an important surgical approach for esophageal cancer. Anastomotic leak is one of its common and serious complications. We assumed that the preoperative risk factors and postoperative indicators would predict or detect anastomotic leak. Methods Between December 2016 and July 2017, patients underwent minimally invasive McKeown esophagectomy were identified and their preoperative variables and postoperative test indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…However, given the operative complexity of esophagectomy and the perioperative resources necessary to care for these patients, this procedure has become increasingly centralized at larger tertiary referral centers, which are more frequently represented in ACS‐NSQIP . Moreover, the rates of anastomotic leak (13.9%) and mortality (2.7%) reported here are similar to prior studies, varying anywhere from 2.96% to 21.9% and 1.0% to 11.6%, respectively . Third, the ACS‐NSQIP does not capture 100% of operative cases performed, which could result in selection bias .…”
Section: Discussionmentioning
confidence: 56%
“…However, given the operative complexity of esophagectomy and the perioperative resources necessary to care for these patients, this procedure has become increasingly centralized at larger tertiary referral centers, which are more frequently represented in ACS‐NSQIP . Moreover, the rates of anastomotic leak (13.9%) and mortality (2.7%) reported here are similar to prior studies, varying anywhere from 2.96% to 21.9% and 1.0% to 11.6%, respectively . Third, the ACS‐NSQIP does not capture 100% of operative cases performed, which could result in selection bias .…”
Section: Discussionmentioning
confidence: 56%
“…Study characteristics of the included studies are shown in Table 1. The role of systemic biomarkers was evaluated separately in fifteen studies, [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] drain fluid in nine [33,44,45,46,47,48,49,50,51], combined scoring systems in three studies [35,41,52], and mediastinal microdialysis [53], urine volatile organic compounds [54] and respiratory index [40] were all evaluated in one study. All studies except three [37,53,54] were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Various definitions of AL were found in the included studies, as shown in Table 2. Six studies [40,42,43,45,49,50] did not mention the median or range concerning the day of AL diagnosis. In the remaining eighteen studies AL was diagnosed with a median on POD 7, ranging between 1 and 30 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few previous reports have described the relationship between AL and the perioperative nutritional status in patients who received esophagectomy for esophageal cancer. Gao et al have evaluated the risk factors of AL in 96 patients who had been diagnosed with esophageal cancer and underwent resection (20). They found that AL occurred in 12.5% and that a lower prealbumin level was an independent risk factor for AL.…”
Section: Discussionmentioning
confidence: 99%